A rare case of tracheal lymphoma presenting with severe tracheal stenosis - Ozgul, Akif; Yasar, Zehra; Sahin, Unal; Acat, Murat; Tecimer, Tulay; Çetinkaya, Erdoğan (European Journal of Oncology and Environmental Health, 2015)
Primary malignant lymphoma of the trachea is rare and its underlying mechanism remains unknown. Primary tracheal tumors are also among very rare causes of airway obstructions. In this case report, a 60 year-old woman who presented with the complaint of dyspnea was reported. A mass narrowing the tracheal lumen posteriorly in the subglottic area and mediastinal lymphadenopathy was detected on computed tomography scan and rijit bronchoscopy was performed. This showed polypoid, variable-sized and irregular nodules causing narrowing of the tracheal lumen through 3 cm segment in the middle part of the trachea and a mass protruding into the tracheal lumen from the posterior part of proximal  trachea. Multiple biopsy was carried out from the nodules and threated airway obstruction with APC. After the removal of the debris, tracheal lumen patency were obtained. The histopathological examination revealed small lymphositic lymphoma of primary non- Hodgkin lymphoma of the trachea. In our knowledge, this is the first primary tracheal small lymphositic lymphoma case in the literature.